Radioactivity and metal concentrations in marine sediments associated with mining activities in Ierissos Gulf, North Aegean Sea, Greece. (October 2016) - Pappa, F.K.; Tsabaris, C.; Ioannidou, A.; Patiris, D.L.; Kaberi, H.; Pashalidis, I.; Eleftheriou, G.; Androulakaki, E.G.; Vlastou, R.
Abstract: Marine sediment samples were collected from Ierissos Gulf, N Aegean Sea, close to the coastal mining facilities. Measurements of radionuclide and metal concentrations, mineral composition and grain size distribution were performed. The concentrations of 226 Ra, 235 U and trace metals showed enhanced values in the port of Stratoni compared with those obtained near to Ierissos port. The dose rates received by marine biota were also calculated by the ERICA Assessment Tool and the results indicated no significant radiological risk. Highlights: Baseline information of radionuclides in a coastal area near a mining site. Trace metals measurements in marine sediment. Dose rates assessment for marine biota using ERICA Assessment Tool.